Nilai Pendidikan Islam dalam Konten TikTok Husain Basyaiban (Analisis Semiotika Roland Barthes) - Aulia, Silfa; Yusuf, Muhammad (Lembaga Yasin AlSys, 2025)
The limited number of studies analyzing the semiotics of Islamic educational values in TikTok content—particularly on the account of Husain Basyaiban—forms the background of this research, considering the significant impact of digital dakwah on Islamic education in the social media era. This study aims to analyze the values of akidah, syariah, and akhlak in Husain Basyaiban’s TikTok content through Roland Barthes’ semiotic approach, focusing on denotative, connotative, and mythological meanings. A qualitative content analysis method was used, with a sample of 16 videos selected through purposive sampling based on criteria such as viewer count, user engagement, and level of controversy. Data were collected through document observation and documentation, and analyzed based on Barthes’ three levels of meaning. The findings reveal that Husain Basyaiban’s TikTok content contains Islamic educational values distributed across three categories: akidah (6 videos), syariah (4 videos), and akhlak (6 videos). These results affirm that digital dakwah can serve as an effective medium for conveying Islamic messages creatively. However, there is a need to deepen the conveyed messages to ensure more comprehensive audience understanding, rather than relying solely on symbolic representation. This study contributes theoretically to the literature on semiotic-based digital dakwah, and practically recommends content optimization through collaboration with Islamic scholars and media literacy education for the public to promote wiser consumption of Islamic content. It also opens avenues for further research on the long-term impact of dakwah content on youth behavior in the digital age.